2020
DOI: 10.1177/1758835919900856
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic aberrations in natural killer/T-cell lymphoma: diagnostic, prognostic and therapeutic implications

Abstract: Natural killer/T-cell lymphoma (NKTCL) is an aggressive malignancy that usually presents in the upper aerodigestive tract. This malignancy shows substantial geographic variability in incidence, and is characterized by Epstein-Barr virus (EBV) infections. Epigenetic aberrations may dysregulate the expression of genes involved in different hallmarks of cancer. A growing body of evidence underscores the importance of epigenetic aberrations in the pathogenesis of NKTCL. Promoter hypermethylation is a common epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 110 publications
(164 reference statements)
1
10
0
Order By: Relevance
“…These findings align with recent NGS studies showing that KMT2D genes are new NKTCL drivers. 52 Chromatin reshaping genes TP53 and ARID1A, which have also been reported in recent studies using NGS, also showed mutations. Further mutations were detected in 18 new genetic candidates whose molecular activity may be linked to the progression of cancer and suggests that these genes may lead to numerous oncogenic instances.…”
Section: Extranodal Nk/t Cell Lymphoma Nasal Typesupporting
confidence: 76%
“…These findings align with recent NGS studies showing that KMT2D genes are new NKTCL drivers. 52 Chromatin reshaping genes TP53 and ARID1A, which have also been reported in recent studies using NGS, also showed mutations. Further mutations were detected in 18 new genetic candidates whose molecular activity may be linked to the progression of cancer and suggests that these genes may lead to numerous oncogenic instances.…”
Section: Extranodal Nk/t Cell Lymphoma Nasal Typesupporting
confidence: 76%
“…Given the lack of response of this GI T-LPD case to a variety of therapeutics, high expression of PD-L1 could be responsible for this patient's poor prognosis as EBV-encoded LMP1 upregulated PD-L1, and elevated PD-L1 resulted in adverse clinical course in NKTCL cases (10). EBV-induced epigenomic aberrations were reported in EBV + malignancies (11). If these epigenomic changes are also present in EBV + GI T-LPD cases, it will be worthwhile to address whether they affect patient survival or not.…”
Section: Case Reportsmentioning
confidence: 96%
“…Epigenetic aberrations play a critical role in tumorigenesis by silencing tumor suppressor genes and altering the regulation of oncogenes. A cohesive understanding of how epigenetic changes drive the ENKTL clone is starting to emerge [32].…”
Section: Epigenetic Aberrations In Enktlmentioning
confidence: 99%